Method for separating and purifying m-dichlorobenzene by adsorption and desorption
Patent Information
- Application Number
- CN202610971038.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本发明的目的是提供一种吸附脱附分离提纯精制间二氯苯的方法,解决现有体系在介孔化提升传质速率与维持微孔形选选择性之间、表面有机聚合物接枝增强选择性与降低再生能耗及保持长期循环稳定性之间、以及吸附剂颗粒强度与低压降要求和高床层传质效率需求之间难以兼顾的耦合矛盾问题
[0078]1.显著提升1,3-二氯苯的吸附选择性和分离纯度:通过钠钾混合离子交换精准调控分子筛超笼窗口的有效孔径和静电环境、碱处理介孔化构建分级孔道加速传质、环氧硅烷桥联聚(4-乙烯吡啶)共价接枝形成分子识别界面,实现了微孔形选、介孔加速扩散和表面分子识别的三重协同选择性增强机制,使得吸附剂对1,3-二氯苯相对于1,2-二氯苯和1,4-二氯苯的选择性系数从现有技术的1.5-2.5提升至3.5-5.0,最终产品纯度可达99.0-99.95wt%,满足精细化工和高端应用对高纯度间二氯苯的严格要求。
Smart Images

Figure CN122958243A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of separation and purification technology, specifically to a method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene. Background Technology
[0002] 1,3-Dichlorobenzene, also known as m-dichlorobenzene, is an important organic chemical intermediate and fine chemical, widely used in the synthesis of pesticides, pharmaceuticals, dyes, and polymer materials. It plays an irreplaceable role, especially in the industrial production of fine chemicals such as isophthalic acid, m-phenylenediamine, and resorcinol. Industrially, 1,3-dichlorobenzene is mainly prepared through the chlorination of benzene. However, this reaction inevitably produces two positional isomers: 1,2-dichlorobenzene (o-dichlorobenzene) and 1,4-dichlorobenzene (p-dichlorobenzene). These three isomers have extremely similar physicochemical properties, with boiling points differing by only about 20°C, forming a near-boiling system. Conventional distillation separation requires a large number of trays and extremely high reflux ratios, resulting in huge energy consumption and low separation efficiency. Therefore, developing efficient, energy-saving, and economical 1,3-dichlorobenzene separation and purification technologies is of great significance for increasing product added value, reducing production costs, and promoting the upgrading of the fine chemical industry. It has become a research hotspot in separation science and engineering and an urgent need in industry.
[0003] Adsorption separation technology, due to its advantages of high selectivity, low energy consumption, and flexible operation, shows promising application prospects in the field of isomer separation. For the separation of dichlorobenzene isomers, existing technologies mainly use zeolite molecular sieves as adsorbents, utilizing their regular pore structure and tunable surface properties to achieve shape-selective separation or separation based on differences in adsorption affinity. For example, Chinese patent application CN1315217A discloses a method for liquid-phase selective adsorption separation of mixed dichlorobenzene using hydrophobic silica zeolite, but this method suffers from drawbacks such as low adsorption capacity and high regeneration energy consumption. The core contradictions faced by existing technologies are as follows: First, mesoporous modification can significantly improve the diffusion rate and adsorption kinetics of molecular sieves, but the introduction of mesopores will weaken the shape-selective effect of the microporous structure and reduce the selectivity for 1,3-dichlorobenzene; Second, grafting organic polymers onto the surface of molecular sieves can enhance the selective adsorption of target components through molecular recognition effects, but the introduction of organic layers will increase the difficulty of regeneration, increase energy consumption, and may lead to performance degradation during recycling due to insufficient thermal stability; Third, the adsorbent needs to have sufficient mechanical strength to withstand industrial packing and fluid scouring, but particle densification will increase bed pressure drop and internal diffusion resistance, affecting mass transfer efficiency. Summary of the Invention
[0004] The purpose of this invention is to provide a method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene, which solves the coupling contradictions in existing systems between improving mass transfer rate through mesoporization and maintaining micropore shape selectivity, enhancing selectivity through surface organic polymer grafting and reducing regeneration energy consumption while maintaining long-term cycle stability, and balancing adsorbent particle strength with the requirements of low pressure drop and high bed mass transfer efficiency.
[0005] This invention employs a synergistic design approach of "hierarchical pore channel control + surface chemical grafting." It precisely controls the cation distribution and framework charge density of the molecular sieve through sodium-potassium mixed ion exchange; mild mesoporization via alkali treatment preserves the micropore shape selection effect while constructing mesoporous mass transfer channels; epoxy silanization creates reactive grafting sites on the molecular sieve surface; and poly(4-vinylpyridine) covalent grafting forms an organic recognition layer with π-π interaction and polar / charge interaction recognition capabilities. This achieves a triple synergy of micropore shape selection, accelerated mesoporous mass transfer, and surface molecular recognition. While significantly improving the adsorption selectivity and mass transfer rate of 1,3-dichlorobenzene, the covalent bond fixation and optimized polymer grafting amount ensure the thermal stability and regenerability of the organic layer. Furthermore, by controlling the particle size distribution and framework mesoporous structure, it balances mechanical strength and mass transfer efficiency, fundamentally overcoming the coupling constraints of existing technologies.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene includes the following steps:
[0008] S1. Providing a raw material mixture comprising 1,3-dichlorobenzene and at least one dichlorobenzene isomer selected from 1,2-dichlorobenzene and 1,4-dichlorobenzene;
[0009] S2. Under adsorption conditions of 60 to 180°C and absolute pressure of 0.20 to 2.00 MPa, the raw material mixture is contacted with an adsorbent to obtain a non-adsorbed phase and an adsorbed phase. The adsorbent comprises a modified 13X molecular sieve material. The modification includes: subjecting the 13X molecular sieve to sodium and potassium ion mixed exchange so that the mass ratio of elemental sodium to elemental potassium in the adsorbent is 0.65:1 to 2:1; subjecting it to alkali treatment to form mesopores so that the mesopore volume of the adsorbent is 0.05 to 0.30 cm³ / g; introducing an epoxy-containing organosilane graft layer on the surface of the molecular sieve; and causing poly(4-vinylpyridine) to undergo a ring-opening reaction with the epoxy groups to form covalent bonds with the surface of the molecular sieve. The epoxy-containing organosilane is 3-glycidyl etheroxypropyltrimethoxysilane, and the mass fraction of poly(4-vinylpyridine) in the adsorbent is 0.5 wt% to 8.0 wt%.
[0010] S3. Desorb the adsorbed phase using a desorbent to obtain a 1,3-dichlorobenzene enriched stream, wherein the desorbent is selected from one or both of ethylbenzene and n-propylbenzene;
[0011] S4. The 1,3-dichlorobenzene enriched stream is subjected to desorbent separation and recovery to obtain the 1,3-dichlorobenzene product and the desorbent is recovered for recycling.
[0012] Furthermore, steps S2 and S3 are performed in a simulated moving bed system.
[0013] Furthermore, the desorption temperature in step S3 is 60 to 200°C, the mass fraction of 1,3-dichlorobenzene in the raw material mixture is 30 wt% to 80 wt%, and the mass ratio of the desorbent to the raw material mixture is 0.5:1 to 5.0:1.
[0014] Furthermore, the desorbent separation and recovery in step S4 is carried out by distillation separation, and the adsorbent is regenerated periodically during continuous operation. The regeneration includes rinsing the adsorbent with the desorbent at a temperature of 60 to 200°C and then drying it. The mass fraction of the 1,3-dichlorobenzene product is 99.0 wt% to 99.95 wt%.
[0015] Furthermore, the adsorbent is prepared through the following steps:
[0016] a) The 13X molecular sieve is subjected to sodium and potassium ion mixed exchange, such that the mass ratio of elemental sodium to elemental potassium in the adsorbent is 0.65:1 to 2:1.
[0017] b) subject the molecular sieve treated in step a) to alkali treatment to form mesopores, such that the mesopore volume of the adsorbent is 0.05 to 0.30 cm³ / g;
[0018] c) Introduce an epoxy-containing organosilane graft layer on the surface of the molecular sieve, wherein the epoxy-containing organosilane is 3-glycidyl etheroxypropyltrimethoxysilane.
[0019] d) The poly(4-vinylpyridine) undergoes a ring-opening reaction with the epoxy group to form a covalent bond with the surface of the molecular sieve.
[0020] Furthermore, the 13X molecular sieve intermediates described in steps a) and b) that have undergone mixing, exchange, and mesoporization are prepared through the following steps:
[0021] A1. Raw material preparation: 13X molecular sieve is used as a solid raw material; sodium chloride and potassium chloride are dissolved in water to obtain an ion exchange solution, wherein the concentration of sodium chloride is 0.10 to 2.00 mol / L and the concentration of potassium chloride is 0.05 to 1.50 mol / L;
[0022] A2. Mixed ion exchange: The 13X molecular sieve is contacted with the ion exchange solution and kept at a temperature of 60 to 95°C for 1.0 to 3.0 h, and repeated 1 to 3 times;
[0023] A3. Washing and drying: The solid is washed with the water and dried to obtain a molecular sieve after mixed ion exchange;
[0024] A4. Alkali treatment for mesoporization: The solid obtained in step A3 is contacted with an aqueous solution of sodium hydroxide, wherein the concentration of sodium hydroxide is 0.05 to 0.20 mol / L, and the contact is maintained at a temperature of 50 to 70°C for 0.5 to 2.0 h.
[0025] A5. Neutralization and post-treatment: The solid-liquid system was neutralized with an aqueous solution of hydrochloric acid to a pH of 6.0 to 8.0, followed by washing and drying to obtain the intermediate;
[0026] The intermediate satisfies the following conditions: the mass ratio of sodium to potassium in the obtained solid is 0.65:1 to 2:1 and the mesopore volume is 0.05 to 0.30 cm³ / g.
[0027] Furthermore, the epoxy-containing organosilane graft layer described in step c) is prepared through the following steps:
[0028] B1. Raw material preparation: The intermediate described in claim 6 is dispersed in a solvent system, wherein the solvent system comprises ethanol and water, the volume ratio of ethanol to water is 70:30 to 95:5, and the solid-liquid ratio of the intermediate to the solvent system is 1g solid to 5 to 30mL solvent;
[0029] B2. pH adjustment: The apparent pH of the solvent system was adjusted to 4.0 to 6.0 using acetic acid;
[0030] B3. Silanization reaction: 3-glycidyl etheroxypropyltrimethoxysilane is added to the solvent system in an amount of 0.5 wt% to 5.0 wt% relative to the dry basis mass of the intermediate, and the reaction is carried out at a temperature of 30 to 60 °C for 1 to 6 h.
[0031] B4. Post-processing: Wash and dry to obtain epoxy silanized intermediate;
[0032] The mass increment of the epoxy silanization intermediate relative to the intermediate used in step B1 is 0.1 wt% to 2.0 wt%.
[0033] Furthermore, the poly(4-vinylpyridine) covalent graft described in step d) is prepared via the following steps:
[0034] C1. Raw material preparation: The epoxy silanization intermediate is dispersed in a mixed solvent, wherein the mixed solvent contains ethanol and acetic acid, and the volume ratio of ethanol to acetic acid is 95:5 to 80:20, and the solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 5 to 30mL solvent.
[0035] C2. Grafting reaction: Poly(4-vinylpyridine) is added to the mixed solvent in an amount of 0.5 wt% to 8.7 wt% relative to the dry basis mass of the epoxy silanization intermediate, and the reaction is carried out at a temperature of 40 to 90 °C for 2 to 12 h.
[0036] C3. Washing and drying: Washing to remove unbound poly(4-vinylpyridine) and drying at a temperature of 60 to 120°C to obtain the adsorbent.
[0037] Furthermore, the adsorbent is pretreated before being used for adsorption-desorption separation, the pretreatment including drying at a temperature of 60 to 150°C for 2 to 12 hours.
[0038] Furthermore, the sieve particle size of the adsorbent is 0.30 to 1.60 mm.
[0039] Furthermore, the sodium to potassium mass ratio Na:K is the mass ratio calculated as elemental sodium to elemental potassium.
[0040] Furthermore, the mesopore volume was determined by nitrogen adsorption-desorption isotherms, and the cumulative pore volume in the range of 2 to 50 nm was calculated based on the desorption branch using the BJH method.
[0041] Furthermore, the dry basis mass of the adsorbent, intermediate, or epoxy silanization intermediate is defined as the mass after drying at a temperature of 60 to 120°C for 2 to 12 hours, cooling to room temperature in a desiccator, and weighing, with the mass change between two consecutive weighings not exceeding 0.1%.
[0042] Furthermore, the mass fraction of poly(4-vinylpyridine) in the adsorbent is calculated based on the dry basis mass of the adsorbent.
[0043] Furthermore, in step A1, the solid-liquid ratio of the 13X molecular sieve to the ion exchange solution is 1g of solid to 5 to 50mL of solution.
[0044] Furthermore, the repetition in step A2 refers to repeating the mixed ion exchange operation after replacing the ion exchange solution with fresh one.
[0045] Furthermore, step A2 is carried out under stirring conditions, and the stirring method is magnetic stirring or mechanical stirring, with a speed of 100 to 600 rpm.
[0046] Furthermore, the washing described in step A3 involves washing the solid with water 3 to 10 times, with each wash volume being 5 to 20 times the mass of the solid, until the chloride ion concentration in the washing solution is below 10 mg / L or the conductivity of the washing solution is below 20 μS / cm.
[0047] Furthermore, the drying process described in step A3 is carried out at a temperature of 60 to 120°C for 2 to 12 hours.
[0048] Furthermore, in step A4, the solid-liquid ratio of the solid to the sodium hydroxide aqueous solution is 1g of solid to 10 to 50mL of solution.
[0049] Furthermore, step A4 is carried out under stirring conditions, and the stirring method is magnetic stirring or mechanical stirring, with a speed of 100 to 600 rpm.
[0050] Furthermore, the concentration of the hydrochloric acid aqueous solution in step A5 is 0.5 to 3.0 mol / L.
[0051] Furthermore, the washing described in step A5 involves washing the solid with water 3 to 10 times, with each wash volume being 5 to 20 times the mass of the solid, until the pH of the washing solution is 6.0 to 8.0 and the conductivity is less than 50 μS / cm.
[0052] Furthermore, the drying process described in step A5 is carried out at a temperature of 60 to 120°C for 2 to 12 hours.
[0053] Furthermore, in step B1, the solid-liquid ratio of the intermediate to the solvent system is 1g solid to 5 to 30mL solvent.
[0054] Furthermore, the pH value of the solvent system mentioned in step B2 is the apparent pH value measured by a pH meter in an ethanol-water mixed solvent.
[0055] Further, the acetic acid mentioned in step B2 is glacial acetic acid or an aqueous solution of acetic acid with a mass fraction of 50% to 99.5%, and the amount added is 0.1 vol% to 3.0 vol% relative to the volume of the solvent system.
[0056] Furthermore, the mass relative to the intermediate solid in step B3 is the dry basis mass relative to the intermediate.
[0057] Furthermore, step B3 is carried out under stirring conditions, and the stirring method is magnetic stirring or mechanical stirring, with a speed of 100 to 500 rpm.
[0058] Furthermore, the washing described in step B4 involves washing the solid 3 to 8 times with anhydrous ethanol or 95% ethanol, with each wash volume being 5 to 15 times the mass of the solid.
[0059] Furthermore, the drying process described in step B4 is carried out at a temperature of 60 to 120°C for 2 to 12 hours.
[0060] Furthermore, the mass increment of the epoxy silanization intermediate relative to the intermediate used in step B1 is defined as the percentage of the difference in dry basis mass between the two intermediates to the dry basis mass of the intermediate used in step B1.
[0061] Furthermore, the mixed solvent in step C1 comprises ethanol and acetic acid in a volume ratio of 95:5 to 80:20.
[0062] Furthermore, in step C1, the solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 5 to 30mL solvent.
[0063] Furthermore, the solid mass relative to the epoxy silanization intermediate mentioned in step C2 is the dry basis mass relative to the epoxy silanization intermediate.
[0064] Furthermore, the poly(4-vinylpyridine) described in step C2 has a number-average molecular weight of 5,000 to 100,000 g / mol or a weight-average molecular weight of 10,000 to 200,000 g / mol.
[0065] Furthermore, step C2 is carried out under stirring conditions, with the stirring method being magnetic stirring or mechanical stirring, and the speed being 100 to 500 rpm.
[0066] Furthermore, the washing described in step C3 involves washing the solid with ethanol 3 to 10 times, with each wash volume being 5 to 15 times the mass of the solid, until the absorbance of the washing solution at 280 nm on a UV-Vis spectrometer is less than 0.05.
[0067] Furthermore, the drying described in step C3 is performed at a temperature of 60 to 120°C for 2 to 12 hours.
[0068] Furthermore, in step S2, the non-adsorbed phase is a fluid material flowing out of the adsorption bed, and the adsorbed phase is an adsorbent bed loaded with at least some components of the raw material mixture.
[0069] Furthermore, the conditions in step S2 also include maintaining the raw material mixture in a liquid phase state.
[0070] Furthermore, the adsorbent phase in step S3 is a solid bed containing the adsorbent and on which at least a portion of the 1,3-dichlorobenzene in the raw material mixture is adsorbed.
[0071] Furthermore, the drying process in the regeneration involves drying at a temperature of 60 to 150°C for 2 to 12 hours.
[0072] Furthermore, the mass fraction of the 1,3-dichlorobenzene product was determined by gas chromatography.
[0073] Furthermore, the gas chromatography method employs a flame ionization detector and calculates the mass percentage of each component using the area normalization method.
[0074] Furthermore, the sieved particle size is the range of particle diameters determined by sieving through a standard sieve.
[0075] As a concept of this invention, a dual-framework regulation strategy of sodium-potassium mixed ion exchange and synergistic alkali treatment for mesoporization is employed, primarily to enhance the synergistic optimization of the adsorbent's shape-selective separation capability and mass transfer kinetics performance. Sodium-potassium mixed ion exchange, by precisely controlling the type, distribution, and charge compensation mode of cations in the 13X molecular sieve framework, optimizes the effective pore size and electric field distribution of the supercage window, enhancing the electrostatic interaction and configuration recognition capability of the 1,3-dichlorobenzene molecule's dipole moment, thereby improving the shape-selective separation effect. Furthermore, it adjusts the framework's silica-alumina ratio and surface hydroxyl density, providing more uniform reactive sites for subsequent alkali treatment for mesoporization and silanization grafting. Alkali treatment for mesoporization, through a controllable framework desilication reaction, generates mesoporous channels of 2 to 50 nm within the grains and grain boundaries while preserving the original microporous structure and crystal framework integrity. This significantly shortens the path length for adsorbate molecules to diffuse from the particle's outer surface to the microporous adsorption sites, substantially reducing diffusion resistance and shortening the adsorption equilibrium time from several hours to tens of minutes. Simultaneously, the introduction of mesopores increases the external specific surface area and the number of accessible micropore inlets, improving the effective utilization rate of the adsorbent. By precisely controlling the mesopore volume within a window range of 0.05 to 0.30 cm³ / g, sufficient mass transfer channels are ensured to avoid diffusion restriction, while excessive mesoporization prevents damage to the microporous framework and shape-selective effect, achieving an optimal balance between shape-selective separation capability and mass transfer rate. Furthermore, the defective hydroxyl and silanol nests on the mesopore surface provide more anchoring sites for subsequent silanization reactions, enhancing the bonding strength between the organic graft layer and the inorganic framework.
[0076] In this invention, there is a significant synergistic effect between sodium-potassium mixed ion exchange modification and alkali treatment for mesoporization, epoxy silanization, and poly(4-vinylpyridine) grafting. Firstly, the sodium-potassium mixed ion exchange establishes a synergistic cation distribution of sodium and potassium ions within the 13X molecular sieve framework. Sodium ions, with their smaller radius (102 pm), tend to occupy hexagonal columnar cages and double six-membered ring sites, while potassium ions, with their larger radius (138 pm), are mainly distributed in the supercage windows and inside the supercages. This hierarchical distribution, on the one hand, maintains the rigidity and shape-selective effect of the microporous framework through the strong electric field of sodium ions; on the other hand, potassium ions regulate the effective pore size and electrostatic environment of the supercage windows, enhancing the electrostatic recognition of 1,3-dichlorobenzene with a specific dipole moment. The synergy between these two factors allows the molecular sieve to achieve excellent configuration selectivity while maintaining structural stability. Secondly, the sodium-potassium mixed exchange alters the distribution of aluminum in the framework and the density of hydroxyl nests, providing more uniform reactive sites for subsequent alkali treatment. This allows for controlled desilication and mesoporization under mild conditions (50-70℃, 0.05-0.20 mol / L NaOH), avoiding framework collapse caused by excessive alkali treatment. Simultaneously, the formation of mesopores exposes more hydroxyl and defect sites within the framework, providing three-dimensional anchoring points for epoxy silanization. Compared to modification only on the outer surface, this mesoporous inner surface silanization significantly improves the loading and distribution uniformity of the organic layer. Furthermore, the epoxy silane layer firmly anchors poly(4-vinylpyridine) to the inorganic framework via covalent bonds. The bond energy of the covalent bonds (approximately 250-350 kJ / mol) is much higher than the van der Waals forces of physical adsorption (approximately 10-40 kJ / mol), which ensures that the organic graft layer maintains structural stability at adsorption-desorption cycling temperatures of 60-200 °C, without desorption or migration. At the same time, the flexible segments of poly(4-vinylpyridine) can partially fill the mesoporous channels, neither blocking the micropore entrances and affecting the shape selection effect, nor hindering the formation of the micropores, but also forming a "molecular recognition gating" effect at the mesopore-micropore interface, preferentially capturing and enriching 1,3-dichlorobenzene molecules. The synergy of these two factors enables the adsorbent to achieve a balance of high selectivity, high capacity, and long cycle life.
[0077] Beneficial technical effects
[0078] 1. Significantly improves the adsorption selectivity and separation purity of 1,3-dichlorobenzene: By precisely controlling the effective pore size and electrostatic environment of the molecular sieve's supercage window through sodium-potassium mixed ion exchange, constructing hierarchical channels through alkali treatment to accelerate mass transfer, and forming a molecular recognition interface through covalent grafting of epoxysilane-bridged poly(4-vinylpyridine), a triple synergistic selectivity enhancement mechanism of micropore shape selection, mesoporous accelerated diffusion, and surface molecular recognition is achieved. This increases the selectivity coefficient of the adsorbent for 1,3-dichlorobenzene relative to 1,2-dichlorobenzene and 1,4-dichlorobenzene from 1.5-2.5 in the existing technology to 3.5-5.0, and the final product purity can reach 99.0-99.95 wt%, meeting the stringent requirements of fine chemicals and high-end applications for high-purity m-dichlorobenzene.
[0079] 2. Significantly shortens adsorption equilibrium time and improves production efficiency: Alkali treatment can controllably generate a hierarchical pore network with a mesoporous volume of 0.05-0.30 cm³ / g while preserving the integrity of the microporous framework. This shortens the diffusion path of adsorbate molecules from the outer surface of the particles to the microporous adsorption sites and reduces diffusion resistance, thereby shortening the time required for adsorption to reach equilibrium and improving production efficiency. This significantly improves the production efficiency of industrial plants and the economic benefits per ton of product.
[0080] 3. Enhanced thermal stability of organic grafted layers and low-energy regeneration: Si-O-Si covalent grafted layers are constructed on the surface of molecular sieves through epoxy silanization, and then CN covalent bonds are formed to fix the polymer chains by the nucleophilic ring-opening reaction of poly(4-vinylpyridine) on epoxy groups. Compared with weak interaction modification methods such as physical adsorption or electrostatic adsorption, the covalent grafted layers maintain structural stability in the adsorption-desorption cycle temperature range of 60-200℃. After 50 adsorption-desorption-regeneration cycles, the performance retention rate is 92.8% to 96.2%, achieving synergistic optimization of high selectivity and low regeneration energy consumption.
[0081] 4. Balancing Adsorbent Particle Mechanical Strength and Bed Mass Transfer Efficiency: By precisely controlling the alkali treatment conditions (NaOH concentration 0.05-0.20 mol / L, temperature 50-70℃, time 0.5-2.0 h), mild mesoporization is achieved. While generating sufficient mesoporous mass transfer channels, the connectivity and mechanical integrity of the crystal skeleton are preserved, ensuring that the compressive strength of the adsorbent particles remains between 25.2 and 32.5 N / particle, meeting the strength requirements for industrial packing and fluid scouring in simulated moving beds. Simultaneously, by controlling the sieve particle size within the range of 0.30-1.60 mm and optimizing the mesopore volume to 0.05-0.30 cm³ / g, the bed pressure drop is controlled within a reasonable range while ensuring sufficient mass transfer efficiency. This achieves a triple balance between particle strength, low pressure drop, and high mass transfer efficiency, significantly reducing the energy consumption and operating costs of industrial plants.
[0082] 5. The process is simple, efficient, and easy to scale up industrially: The adsorbent preparation process of this invention adopts conventional chemical unit operations (ion exchange, alkali treatment, silanization, polymer grafting), and the raw materials are readily available (sodium chloride, potassium chloride, sodium hydroxide, 3-glycidyl etheroxypropyltrimethoxysilane, and poly(4-vinylpyridine) are all commercially available chemicals). The reaction conditions are mild (temperature 30-95℃, atmospheric pressure or slightly positive pressure), requiring no special equipment or harsh operating conditions, and it is easy to scale up from laboratory scale to industrial scale. The adsorption and separation process adopts mature simulated moving bed technology, and the desorbent ethylbenzene or n-propylbenzene can be distilled and recycled, thereby reducing solvent consumption and emissions, meeting the requirements of green chemical industry and sustainable development, and has good prospects for industrial application and economic promotion value. Attached Figure Description
[0083] Figure 1 This is the XRD pattern of X-ray diffraction.
[0084] Figure 2 This is a high-resolution XPS scan of sodium (Na) from X-ray photoelectron spectroscopy.
[0085] Figure 3 This is a high-resolution XPS scan of potassium (K) in X-ray photoelectron spectroscopy.
[0086] Figure 4 This is a BJH method diagram of the nitrogen adsorption-desorption isotherm.
[0087] Figure 5 The BJH pore size distribution curves for the nitrogen adsorption-desorption isotherm are shown.
[0088] Figure 6 The BJH cumulative pore volume distribution curve is shown for the nitrogen adsorption-desorption isotherm.
[0089] Figure 7 A comparison chart of grafting amounts for determining the grafting amount of poly(4-vinylpyridine).
[0090] Figure 8 This is a macroscopic optical photograph of the adsorbent in Example 1.
[0091] Figure 9 This is a scanning electron microscope (SEM) image of the adsorbent in Example 1.
[0092] Figure 10 This is a transmission electron microscope (TEM) image of the adsorbent in Example 1. Detailed Implementation
[0093] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0094] Example 1
[0095] This embodiment provides a method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene, with the following specific steps:
[0096] Step S1: Preparation of raw material mixture
[0097] A raw material mixture is provided. In this embodiment, the raw material mixture contains 1,3-dichlorobenzene, 1,2-dichlorobenzene and 1,4-dichlorobenzene, wherein the mass fraction of 1,3-dichlorobenzene is 55 wt%.
[0098] Step S2: Adsorbent preparation
[0099] The adsorbent in this embodiment is prepared through the following steps:
[0100] (a) Sodium-potassium mixed ion exchange
[0101] A1. Raw material preparation: 13X molecular sieve is used as the solid raw material; sodium chloride and potassium chloride are dissolved in deionized water to obtain an ion exchange solution, wherein the concentration of sodium chloride is 1.00 mol / L and the concentration of potassium chloride is 0.80 mol / L. The solid-liquid ratio of 13X molecular sieve to ion exchange solution is 1 g of solid to 25 mL of solution.
[0102] A2. Mixed Ion Exchange: 13X molecular sieves were contacted with the ion exchange solution and kept at 78°C and 300 rpm under magnetic stirring for 2.0 h. The mixed ion exchange process was repeated twice after replacing the ion exchange solution.
[0103] A3. Washing and Drying: The solid was washed 6 times with deionized water, each wash volume being 12 times the mass of the solid, until the chloride ion concentration in the washing solution was below 10 mg / L and the conductivity of the washing solution was below 20 μS / cm. The solid was then dried at 90℃ for 7 hours to obtain the mixed ion-exchange molecular sieve.
[0104] A4. Alkali treatment for mesoporization: The solid obtained in step A3 is contacted with an aqueous solution of sodium hydroxide with a concentration of 0.12 mol / L. The solid-liquid ratio of the solid to the aqueous solution of sodium hydroxide is 1 g of solid to 30 mL of solution. The mixture is kept at 60 °C for 1.2 h under magnetic stirring (300 rpm).
[0105] A5. Neutralization and Post-treatment: The solid-liquid system was neutralized to pH 7.0 with a 1.8 mol / L hydrochloric acid aqueous solution. The solid was then washed seven times with deionized water, each wash volume being 12 times the solid mass, until the pH of the washing solution was between 6.0 and 8.0 and the conductivity was below 50 μS / cm. The mixture was dried at 90℃ for 7 h to obtain a mixed ion-exchanged and mesoporous 13X molecular sieve intermediate. The mass ratio of sodium to potassium in the obtained intermediate was 1.2:1 (Na:K), and the mesopore volume was 0.18 cm³ / g (determined by nitrogen adsorption-desorption isotherms, and the cumulative pore volume in the pore size range of 2 to 50 nm was calculated using the BJH method based on the desorption branch).
[0106] (b) Epoxysilane grafting
[0107] B1. Raw material preparation: The above intermediate is dispersed in a solvent system. In this embodiment, the solvent system contains ethanol and water, with a volume ratio of ethanol to water of 82:18. The solid-liquid ratio of the intermediate to the solvent system is 1g of solid to 18mL of solvent.
[0108] B2. pH adjustment: The apparent pH of the solvent system was adjusted to 5.0 using glacial acetic acid, with the amount of acetic acid added being 1.5 vol relative to the volume of the solvent system.
[0109] B3. Silanization reaction: 3-glycidyl etheroxypropyltrimethoxysilane was added to the solvent system at an amount of 2.8 wt% relative to the dry basis mass of the intermediate, and the reaction was carried out at 45 °C for 3.5 h under magnetic stirring (300 rpm).
[0110] B4. Post-treatment: The solid was washed five times with anhydrous ethanol, each wash volume being 10 times the mass of the solid. It was then dried at 90°C for 7 hours to obtain the epoxy silanized intermediate. In this embodiment, the mass increment of the epoxy silanized intermediate relative to the intermediate used in step B1 was 1.0 wt% (mass increment is defined as the percentage of the difference in dry basis mass between the two intermediates to the dry basis mass of the intermediate used in step B1).
[0111] (c) Covalent grafting of poly(4-vinylpyridine)
[0112] C1. Raw material preparation: The epoxy silanization intermediate is dispersed in a mixed solvent. In this embodiment, the mixed solvent contains ethanol and acetic acid, with a volume ratio of ethanol to acetic acid of 87:13. The solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 18mL solvent.
[0113] C2. Grafting reaction: Poly(4-vinylpyridine) with a number average molecular weight of 50,000 g / mol was added to the mixed solvent at an amount of 5.0 wt% relative to the dry basis mass of the epoxy silanization intermediate. The reaction was carried out under magnetic stirring (300 rpm) at 65 °C for 7 h, so that the poly(4-vinylpyridine) and epoxy groups underwent a ring-opening reaction and formed covalent bonds with the surface of the molecular sieve.
[0114] C3. Washing and Drying: The solid was washed seven times with ethanol, each wash volume being 10 times the mass of the solid, until the absorbance of the washing solution at 280 nm on a UV-Vis spectrometer was less than 0.05, to remove unbound poly(4-vinylpyridine). The adsorbent was dried at 90°C for 7 hours. In this embodiment, the mass fraction of poly(4-vinylpyridine) in the adsorbent was 4.5 wt% (calculated based on the dry weight of the adsorbent).
[0115] Adsorbent pretreatment and sieving:
[0116] The above adsorbent was pretreated before being used for adsorption-desorption separation by drying at 105°C for 7 hours. Adsorbent particles with a sieve size of 0.95 mm were obtained by sieving (the sieve size was determined by sieving using a standard sieve).
[0117] Step S3: Adsorption Separation
[0118] In the simulated moving bed system, under the conditions of an adsorption temperature of 120°C and an absolute pressure of 1.10 MPa, the raw material mixture is kept in a liquid phase, allowing it to contact the adsorbent and obtain a non-adsorbed phase and an adsorbed phase. In this embodiment, the non-adsorbed phase is the fluid material flowing out of the adsorption bed, and the adsorbed phase is a solid bed containing the adsorbent and on which at least a portion of the 1,3-dichlorobenzene in the raw material mixture is adsorbed.
[0119] Step S4: Desorption
[0120] In the simulated moving bed system, a desorbent is used to desorb the adsorbed phase to obtain a 1,3-dichlorobenzene enriched stream. In this embodiment, the desorbent is ethylbenzene, the desorption temperature is 130°C, and the mass ratio of the desorbent to the raw material mixture is 2.5:1.
[0121] Step S5: Desorbent separation and recovery
[0122] The 1,3-dichlorobenzene enriched stream was separated by distillation to recover the desorbent, yielding the 1,3-dichlorobenzene product, and the desorbent was recovered for recycling. In this embodiment, the mass fraction of the 1,3-dichlorobenzene product was 99.5 wt% (determined by gas chromatography using a flame ionization detector, with the mass percentage of each component calculated using the area normalization method).
[0123] Adsorbent regeneration:
[0124] In this embodiment, the adsorbent is regenerated periodically during continuous operation. The regeneration includes rinsing the adsorbent with ethylbenzene at 130°C and then drying it at 105°C for 7 hours.
[0125] Features of Example 1: This example uses moderate parameter configurations: adsorption temperature 120℃, pressure 1.10 MPa, Na:K mass ratio of 1.2:1 in the adsorbent, mesopore volume 0.18 cm³ / g, poly(4-vinylpyridine) content 4.5 wt%, desorption temperature 130℃, and desorbent to feedstock mass ratio 2.5:1, yielding 1,3-dichlorobenzene with a purity of 99.5 wt%. This parameter combination represents a stable and reliable process route, with parameters at moderate levels, a wide process operating window, and good reproducibility. It is suitable for medium-scale industrial production, and particularly suitable for fine chemical separation scenarios requiring product purity of approximately 99.5 wt% and pursuing process stability and long-term operation.
[0126] Example 2
[0127] This embodiment provides a method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene, with the following specific steps:
[0128] Step S1: Preparation of raw material mixture
[0129] A raw material mixture is provided. In this embodiment, the raw material mixture contains 1,3-dichlorobenzene, 1,2-dichlorobenzene and 1,4-dichlorobenzene, wherein the mass fraction of 1,3-dichlorobenzene is 45 wt%.
[0130] Step S2: Adsorbent preparation
[0131] The adsorbent in this embodiment is prepared through the following steps:
[0132] (a) Sodium-potassium mixed ion exchange
[0133] A1. Raw material preparation: 13X molecular sieve is used as the solid raw material; sodium chloride and potassium chloride are dissolved in deionized water to obtain an ion exchange solution, wherein the concentration of sodium chloride is 0.60 mol / L and the concentration of potassium chloride is 0.50 mol / L. The solid-liquid ratio of 13X molecular sieve to ion exchange solution is 1 g of solid to 35 mL of solution.
[0134] A2. Mixed Ion Exchange: 13X molecular sieves were contacted with the ion exchange solution and kept at 70°C and 250 rpm under magnetic stirring for 1.5 hours. The mixed ion exchange process was repeated twice after replacing the ion exchange solution.
[0135] A3. Washing and Drying: The solid was washed five times with deionized water, each wash volume being 15 times the mass of the solid, until the chloride ion concentration in the washing solution was below 10 mg / L and the conductivity of the washing solution was below 20 μS / cm. The solid was then dried at 80℃ for 5 hours to obtain the mixed ion-exchange molecular sieve.
[0136] A4. Alkali treatment for mesoporization: The solid obtained in step A3 is contacted with an aqueous solution of sodium hydroxide with a concentration of 0.08 mol / L. The solid-liquid ratio of the solid to the aqueous solution of sodium hydroxide is 1 g of solid to 35 mL of solution. The mixture is kept at 55 °C for 0.8 h under magnetic stirring (250 rpm).
[0137] A5. Neutralization and Post-treatment: The solid-liquid system was neutralized to pH 6.5 using a 1.2 mol / L hydrochloric acid aqueous solution. The solid was then washed five times with deionized water, each wash volume being 15 times the solid mass, until the pH of the washing solution was between 6.0 and 8.0 and the conductivity was below 50 μS / cm. The intermediate was dried at 80℃ for 5 h to obtain a mixed ion-exchanged and mesoporous 13X molecular sieve intermediate. The mass ratio of sodium to potassium in the obtained intermediate was 0.90:1, and the mesopore volume was 0.12 cm³ / g (determined by nitrogen adsorption-desorption isotherms, and the cumulative pore volume in the pore size range of 2 to 50 nm was calculated using the BJH method based on the desorption branch).
[0138] (b) Epoxysilane grafting
[0139] B1. Raw material preparation: The above intermediate is dispersed in a solvent system. In this embodiment, the solvent system contains ethanol and water, with a volume ratio of ethanol to water of 75:25. The solid-liquid ratio of the intermediate to the solvent system is 1g of solid to 22mL of solvent.
[0140] B2. pH adjustment: The apparent pH of the solvent system was adjusted to 4.5 using glacial acetic acid, with the amount of acetic acid added being 0.8 vol relative to the volume of the solvent system.
[0141] B3. Silanization reaction: 3-glycidyl etheroxypropyltrimethoxysilane was added to the solvent system at an amount of 1.5 wt% relative to the dry basis mass of the intermediate, and the reaction was carried out at 38 °C for 2 h under magnetic stirring (250 rpm).
[0142] B4. Post-treatment: The solid was washed four times with anhydrous ethanol, with each wash volume being eight times the mass of the solid. It was then dried at 80°C for 5 hours to obtain the epoxy silanized intermediate. In this embodiment, the mass increment of the epoxy silanized intermediate relative to the intermediate used in step B1 was 0.5 wt% (mass increment is defined as the percentage of the difference in dry basis mass between the two intermediates to the dry basis mass of the intermediate used in step B1).
[0143] (c) Covalent grafting of poly(4-vinylpyridine)
[0144] C1. Raw material preparation: The epoxy silanization intermediate is dispersed in a mixed solvent. In this embodiment, the mixed solvent contains ethanol and acetic acid, with a volume ratio of ethanol to acetic acid of 92:8. The solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 22mL solvent.
[0145] C2. Grafting reaction: Poly(4-vinylpyridine) with a number average molecular weight of 30,000 g / mol was added to the mixed solvent at an amount of 3.0 wt% relative to the dry basis mass of the epoxy silanization intermediate. The reaction was carried out under magnetic stirring (250 rpm) at 50 °C for 4 h, so that the poly(4-vinylpyridine) and epoxy groups underwent a ring-opening reaction and formed covalent bonds with the surface of the molecular sieve.
[0146] C3. Washing and Drying: The solid was washed five times with ethanol, each time by a volume eight times the mass of the solid, until the absorbance of the washing solution at 280 nm on a UV-Vis spectrometer was less than 0.05, to remove unbound poly(4-vinylpyridine). The adsorbent was dried at 80°C for 5 hours. In this embodiment, the mass fraction of poly(4-vinylpyridine) in the adsorbent was 2.5 wt% (calculated based on the dry weight of the adsorbent).
[0147] Adsorbent pretreatment and sieving:
[0148] The above adsorbent was pretreated by drying at 85°C for 5 hours before being used for adsorption-desorption separation. Adsorbent particles with a sieve size of 0.65 mm were obtained by sieving (the sieve size was determined by sieving using a standard sieve).
[0149] Step S3: Adsorption Separation
[0150] In the simulated moving bed system, under the conditions of an adsorption temperature of 90°C and an absolute pressure of 0.70 MPa, the raw material mixture is kept in a liquid phase, allowing it to contact the adsorbent and obtain a non-adsorbed phase and an adsorbed phase. In this embodiment, the non-adsorbed phase is the fluid material flowing out of the adsorption bed, and the adsorbed phase is a solid bed containing the adsorbent and on which at least a portion of the 1,3-dichlorobenzene in the raw material mixture is adsorbed.
[0151] Step S4: Desorption
[0152] In the simulated moving bed system, a desorbent is used to desorb the adsorbed phase to obtain a 1,3-dichlorobenzene enriched stream. In this embodiment, the desorbent is n-propylbenzene, the desorption temperature is 110°C, and the mass ratio of the desorbent to the raw material mixture is 1.5:1.
[0153] Step S5: Desorbent separation and recovery
[0154] The 1,3-dichlorobenzene enriched stream was separated by distillation to recover the desorbent, yielding the 1,3-dichlorobenzene product, and the desorbent was recovered for recycling. In this embodiment, the mass fraction of the 1,3-dichlorobenzene product was 99.3 wt% (determined by gas chromatography using a flame ionization detector, with the mass percentage of each component calculated using the area normalization method).
[0155] Adsorbent regeneration:
[0156] In this embodiment, the adsorbent is regenerated periodically during continuous operation. The regeneration includes rinsing the adsorbent with n-propylbenzene at a temperature of 110°C and then drying it at a temperature of 85°C for 5 hours.
[0157] Features of Example 2: This example employs mild operating conditions: adsorption temperature 90℃, pressure 0.70 MPa, Na:K mass ratio of 0.90:1, mesopore volume 0.12 cm³ / g, poly(4-vinylpyridine) content 2.5 wt% in the adsorbent, desorption temperature 110℃, and desorbent to feed mass ratio 1.5:1, yielding 1,3-dichlorobenzene with a purity of 99.3 wt%. This parameter combination represents a low-energy, mild process route, employing a lower ion exchange concentration, milder alkali treatment conditions, and a lower silanization reaction temperature. The adsorption and separation stages operate at relatively low temperatures and pressures, making it suitable for energy-sensitive applications with low 1,3-dichlorobenzene content (around 45 wt%) in the feedstock, prioritizing economic efficiency in small-scale or pilot-scale plants. It is particularly suitable for heat-sensitive material systems or applications with lower equipment pressure resistance requirements.
[0158] Example 3
[0159] This embodiment provides a method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene, with the following specific steps:
[0160] Step S1: Preparation of raw material mixture
[0161] A raw material mixture is provided. In this embodiment, the raw material mixture contains 1,3-dichlorobenzene, 1,2-dichlorobenzene and 1,4-dichlorobenzene, wherein the mass fraction of 1,3-dichlorobenzene is 65 wt%.
[0162] Step S2: Adsorbent preparation
[0163] The adsorbent in this embodiment is prepared through the following steps:
[0164] (a) Sodium-potassium mixed ion exchange
[0165] A1. Raw material preparation: 13X molecular sieve is used as the solid raw material; sodium chloride and potassium chloride are dissolved in deionized water to obtain an ion exchange solution, wherein the concentration of sodium chloride is 1.50 mol / L and the concentration of potassium chloride is 1.10 mol / L. The solid-liquid ratio of 13X molecular sieve to ion exchange solution is 1g solid to 15mL solution.
[0166] A2. Mixed Ion Exchange: 13X molecular sieves were contacted with the ion exchange solution and kept at 88°C for 2.5 hours under mechanical stirring at 450 rpm. The mixed ion exchange process was repeated three times after replacing the ion exchange solution.
[0167] A3. Washing and Drying: The solid was washed 8 times with deionized water, each wash volume being 18 times the mass of the solid, until the chloride ion concentration in the washing solution was below 10 mg / L and the conductivity of the washing solution was below 20 μS / cm. The solid was then dried at 105℃ for 9 hours to obtain the mixed ion-exchange molecular sieve.
[0168] A4. Alkali treatment for mesoporization: The solid obtained in step A3 is contacted with an aqueous solution of sodium hydroxide with a concentration of 0.16 mol / L. The solid-liquid ratio of the solid to the aqueous solution of sodium hydroxide is 1 g of solid to 20 mL of solution. The mixture is kept at 65 °C for 1.6 h under mechanical stirring (450 rpm).
[0169] A5. Neutralization and Post-treatment: The solid-liquid system was neutralized to pH 7.5 with a 2.5 mol / L hydrochloric acid aqueous solution. The solid was then washed eight times with deionized water, each wash volume being 18 times the solid mass, until the pH of the washing solution was between 6.0 and 8.0 and the conductivity was below 50 μS / cm. The intermediate was dried at 105℃ for 9 h to obtain a mixed ion-exchanged and mesoporous 13X molecular sieve intermediate. The mass ratio of sodium to potassium in the obtained intermediate was 1.6:1, and the mesopore volume was 0.24 cm³ / g (determined by nitrogen adsorption-desorption isotherms, and the cumulative pore volume in the pore size range of 2 to 50 nm was calculated using the BJH method based on the desorption branch).
[0170] (b) Epoxysilane grafting
[0171] B1. Raw material preparation: The above intermediate is dispersed in a solvent system. In this embodiment, the solvent system contains ethanol and water, with a volume ratio of ethanol to water of 90:10. The solid-liquid ratio of the intermediate to the solvent system is 1g of solid to 12mL of solvent.
[0172] B2. pH adjustment: The apparent pH of the solvent system was adjusted to 5.5 using glacial acetic acid, with the amount of acetic acid added being 2.2 vol relative to the volume of the solvent system.
[0173] B3. Silanization reaction: 3-glycidyl etheroxypropyltrimethoxysilane was added to the solvent system at an amount of 4.0 wt% relative to the dry basis mass of the intermediate, and the reaction was carried out at 52 °C for 5 h under mechanical stirring (400 rpm).
[0174] B4. Post-treatment: The solid was washed 7 times with anhydrous ethanol, with each wash volume being 13 times the mass of the solid. It was then dried at 105°C for 9 hours to obtain the epoxy silanized intermediate. In this embodiment, the mass increment of the epoxy silanized intermediate relative to the intermediate used in step B1 was 1.6 wt% (mass increment is defined as the percentage of the difference in dry basis mass between the two intermediates to the dry basis mass of the intermediate used in step B1).
[0175] (c) Covalent grafting of poly(4-vinylpyridine)
[0176] C1. Raw material preparation: The epoxy silanization intermediate is dispersed in a mixed solvent. In this embodiment, the mixed solvent contains ethanol and acetic acid, with a volume ratio of ethanol to acetic acid of 83:17. The solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 12mL solvent.
[0177] C2. Grafting reaction: Poly(4-vinylpyridine) with a number average molecular weight of 75,000 g / mol was added to the mixed solvent at an amount of 7.0 wt% relative to the dry basis mass of the epoxy silanization intermediate. The reaction was carried out under mechanical stirring (400 rpm) at 78 °C for 10 h, so that the poly(4-vinylpyridine) and epoxy groups underwent a ring-opening reaction and formed covalent bonds with the surface of the molecular sieve.
[0178] C3. Washing and Drying: The solid was washed 8 times with ethanol, each wash volume being 13 times the mass of the solid, until the absorbance of the washing solution at 280 nm on a UV-Vis spectrometer was less than 0.05, to remove unbound poly(4-vinylpyridine). The adsorbent was dried at 105°C for 9 hours. In this embodiment, the mass fraction of poly(4-vinylpyridine) in the adsorbent was 6.5 wt% (calculated based on the dry weight of the adsorbent).
[0179] Adsorbent pretreatment and sieving:
[0180] The above adsorbent was pretreated before being used for adsorption-desorption separation by drying at 125°C for 9 hours. Adsorbent particles with a sieve diameter of 1.25 mm were obtained by sieving (the sieve diameter was determined by standard sieve mesh).
[0181] Step S3: Adsorption Separation
[0182] In a simulated moving bed system, under adsorption conditions of 150°C and 1.50 MPa, the raw material mixture is kept in a liquid phase, allowing it to contact the adsorbent and obtain a non-adsorbed phase and an adsorbed phase. In this embodiment, the non-adsorbed phase is the fluid material flowing out of the adsorption bed, and the adsorbed phase is a solid bed containing the adsorbent and on which at least a portion of the 1,3-dichlorobenzene in the raw material mixture is adsorbed.
[0183] Step S4: Desorption
[0184] In the simulated moving bed system, a desorbent is used to desorb the adsorbed phase to obtain a 1,3-dichlorobenzene enriched stream. In this embodiment, the desorbent is a mixture of ethylbenzene and n-propylbenzene (mass ratio of 60:40), the desorption temperature is 170°C, and the mass ratio of the desorbent to the raw material mixture is 3.5:1.
[0185] Step S5: Desorbent separation and recovery
[0186] The 1,3-dichlorobenzene enriched stream was separated by distillation to recover the desorbent, yielding the 1,3-dichlorobenzene product, and the desorbent was recovered for recycling. In this embodiment, the mass fraction of the 1,3-dichlorobenzene product was 99.75 wt% (determined by gas chromatography using a flame ionization detector, with the mass percentage of each component calculated using the area normalization method).
[0187] Adsorbent regeneration:
[0188] In this embodiment, the adsorbent is regenerated periodically during continuous operation. The regeneration includes rinsing the adsorbent with a mixture of ethylbenzene and n-propylbenzene at a temperature of 170°C and then drying it at a temperature of 125°C for 9 hours.
[0189] Example 3 Features: This example employs enhanced operating conditions: adsorption temperature 150℃, pressure 1.50 MPa, Na:K mass ratio of 1.6:1 in the adsorbent, mesopore volume 0.24 cm³ / g, poly(4-vinylpyridine) content 6.5 wt%, desorption temperature 170℃, and desorbent to feedstock mass ratio 3.5:1, yielding a high-purity 1,3-dichlorobenzene product with a purity of 99.75 wt%. This parameter combination represents a high-performance enhanced process route, employing higher ion exchange concentrations, stronger alkaline treatment conditions, higher silanization reagent dosage, and longer grafting reaction time. The adsorption and separation stages utilize higher temperatures and pressures, making it suitable for large-scale industrial production where the feedstock has a high 1,3-dichlorobenzene content (65 wt%) and strict purity requirements (above 99.75 wt%). It is particularly suitable for high-value-added fine chemical fields with extremely high purity requirements, such as pharmaceutical intermediates and electronic chemicals.
[0190] Example 4
[0191] This embodiment provides a method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene, with the following specific steps:
[0192] Step S1: Preparation of raw material mixture
[0193] A raw material mixture is provided. In this embodiment, the raw material mixture contains 1,3-dichlorobenzene, 1,2-dichlorobenzene and 1,4-dichlorobenzene, wherein the mass fraction of 1,3-dichlorobenzene is 50 wt%.
[0194] Step S2: Adsorbent preparation
[0195] The adsorbent in this embodiment is prepared through the following steps:
[0196] (a) Sodium-potassium mixed ion exchange
[0197] A1. Raw material preparation: 13X molecular sieve is used as the solid raw material; sodium chloride and potassium chloride are dissolved in deionized water to obtain an ion exchange solution, wherein the concentration of sodium chloride is 1.75 mol / L and the concentration of potassium chloride is 1.00 mol / L. The solid-liquid ratio of 13X molecular sieve to ion exchange solution is 1g solid to 18mL solution.
[0198] A2. Mixed Ion Exchange: 13X molecular sieves were contacted with the ion exchange solution and kept at 500 rpm and 92°C for 2.8 hours under mechanical stirring. The mixed ion exchange process was repeated three times after replacing the ion exchange solution.
[0199] A3. Washing and Drying: The solid was washed nine times with deionized water, each wash volume being 10 times the mass of the solid, until the chloride ion concentration in the washing solution was below 10 mg / L and the conductivity of the washing solution was below 20 μS / cm. The solid was then dried at 110℃ for 10 h to obtain the mixed ion-exchange molecular sieve.
[0200] A4. Alkali treatment for mesoporization: The solid obtained in step A3 is contacted with an aqueous solution of sodium hydroxide with a concentration of 0.06 mol / L. The solid-liquid ratio of the solid to the aqueous solution of sodium hydroxide is 1 g of solid to 25 mL of solution. The mixture is kept at 68 °C for 1.8 h under mechanical stirring (500 rpm).
[0201] A5. Neutralization and Post-treatment: The solid-liquid system was neutralized with a 2.0 mol / L hydrochloric acid aqueous solution to a pH of 7.2. The solid was then washed nine times with deionized water, each wash volume being 10 times the solid mass, until the pH of the washing solution was between 6.0 and 8.0 and the conductivity was below 50 μS / cm. The mixture was dried at 110℃ for 10 h to obtain a mixed ion-exchanged and mesoporous 13X molecular sieve intermediate. The mass ratio of sodium to potassium in the obtained intermediate was 1.85:1, and the mesopore volume was 0.20 cm³ / g (determined by nitrogen adsorption-desorption isotherms, and the cumulative pore volume in the pore size range of 2 to 50 nm was calculated using the BJH method based on the desorption branch).
[0202] (b) Epoxysilane grafting
[0203] B1. Raw material preparation: The above intermediate is dispersed in a solvent system. In this embodiment, the solvent system contains ethanol and water, with a volume ratio of ethanol to water of 93:7. The solid-liquid ratio of the intermediate to the solvent system is 1g of solid to 8mL of solvent.
[0204] B2. pH adjustment: The apparent pH of the solvent system was adjusted to 5.8 using glacial acetic acid, with the amount of acetic acid added being 2.7 vol relative to the volume of the solvent system.
[0205] B3. Silanization reaction: 3-glycidyl etheroxypropyltrimethoxysilane was added to the solvent system at an amount of 4.5 wt% relative to the dry basis mass of the intermediate, and the reaction was carried out at 56 °C for 5.5 h under mechanical stirring (450 rpm).
[0206] B4. Post-treatment: The solid was washed 8 times with anhydrous ethanol, with each wash volume being 14 times the mass of the solid. It was then dried at 115°C for 11 hours to obtain the epoxy silanized intermediate. In this embodiment, the mass increment of the epoxy silanized intermediate relative to the intermediate used in step B1 was 1.8 wt% (mass increment is defined as the percentage of the difference in dry basis mass between the two intermediates to the dry basis mass of the intermediate used in step B1).
[0207] (c) Covalent grafting of poly(4-vinylpyridine)
[0208] C1. Raw material preparation: The epoxy silanization intermediate is dispersed in a mixed solvent. In this embodiment, the mixed solvent contains ethanol and acetic acid, with a volume ratio of ethanol to acetic acid of 81:19. The solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 8mL solvent.
[0209] C2. Grafting reaction: Poly(4-vinylpyridine) with a number average molecular weight of 90,000 g / mol was added to the mixed solvent at an amount of 8.2 wt% relative to the dry basis mass of the epoxy silanization intermediate. The reaction was carried out under mechanical stirring (450 rpm) at 85 °C for 11 h, so that the poly(4-vinylpyridine) and epoxy groups underwent a ring-opening reaction and formed covalent bonds with the surface of the molecular sieve.
[0210] C3. Washing and Drying: The solid was washed nine times with ethanol, each wash volume being 14 times the mass of the solid, until the absorbance of the washing solution at 280 nm on a UV-Vis spectrometer was less than 0.05, to remove unbound poly(4-vinylpyridine). The adsorbent was dried at 115°C for 11 hours. In this embodiment, the mass fraction of poly(4-vinylpyridine) in the adsorbent was 7.5 wt% (calculated based on the dry weight of the adsorbent).
[0211] Adsorbent pretreatment and sieving:
[0212] The above adsorbent was pretreated before being used for adsorption-desorption separation by drying at 140℃ for 11 hours. Adsorbent particles with a sieve size of 1.45 mm were obtained by sieving (the sieve size was determined by sieving using a standard sieve).
[0213] Step S3: Adsorption Separation
[0214] In the simulated moving bed system, under the conditions of an adsorption temperature of 165°C and an absolute pressure of 1.20 MPa, the raw material mixture is kept in a liquid phase, allowing it to contact the adsorbent and obtain a non-adsorbed phase and an adsorbed phase. In this embodiment, the non-adsorbed phase is the fluid material flowing out of the adsorption bed, and the adsorbed phase is a solid bed containing the adsorbent and on which at least a portion of the 1,3-dichlorobenzene in the raw material mixture is adsorbed.
[0215] Step S4: Desorption
[0216] In the simulated moving bed system, a desorbent is used to desorb the adsorbed phase to obtain a 1,3-dichlorobenzene enriched stream. In this embodiment, the desorbent is ethylbenzene, the desorption temperature is 140°C, and the mass ratio of the desorbent to the raw material mixture is 0.8:1.
[0217] Step S5: Desorbent separation and recovery
[0218] The 1,3-dichlorobenzene enriched stream was separated by distillation to recover the desorbent, yielding the 1,3-dichlorobenzene product, and the desorbent was recovered for recycling. In this embodiment, the mass fraction of the 1,3-dichlorobenzene product was 99.6 wt% (determined by gas chromatography using a flame ionization detector, with the mass percentage of each component calculated using the area normalization method).
[0219] Adsorbent regeneration:
[0220] In this embodiment, the adsorbent is regenerated periodically during continuous operation. The regeneration includes rinsing the adsorbent with ethylbenzene at 185°C and then drying it at 140°C for 11 hours.
[0221] Features of Example 4: This example uses an extended parameter range design, with an adsorption temperature of 165℃, a pressure of 1.20MPa, a Na:K mass ratio of 1.85:1 in the adsorbent, a mesopore volume of 0.20cm³ / g, a poly(4-vinylpyridine) content of 7.5wt%, a desorption temperature of 140℃, and a desorbent to raw material mass ratio of 0.8:1, to obtain a 1,3-dichlorobenzene product with a purity of 99.6wt%. This parameter combination explores an extended range of process parameters. Ion exchange employs a near-saturated high-concentration salt solution, a high exchange temperature, and a long exchange time. Alkali treatment uses a strategy of lower concentration but higher temperature and a longer time. Silanization and polymer grafting use parameters close to the upper limit of the formulation dosage. The adsorption separation stage uses a higher temperature but with a lower desorbent dosage to reduce separation costs. This process route verifies the applicability and flexibility of the technical solution. It is suitable for special application scenarios with medium raw material composition (50wt% 1,3-dichlorobenzene content) and a pursuit of desorbent-saving economic operation mode. It is particularly suitable for industrial plants with high desorbent recovery costs or special requirements for adsorbent performance.
[0222] Performance testing:
[0223] Experiment 1: Determination of purity of 1,3-dichlorobenzene product
[0224] This experiment used 1,3-dichlorobenzene recovered by distillation as the test object, aiming to evaluate the separation and purification effect of the method of this invention on m-dichlorobenzene and quantify the product purity. Gas chromatography was used to separate the components in the mixture, and the analysis was performed using the principles of retention time for qualitative analysis and peak area normalization for quantitative analysis. The specific experimental method was as follows: a gas chromatograph equipped with a flame ionization detector (FID) was used, with a capillary column (30m × 0.32mm × 0.25μm), nitrogen as the carrier gas (flow rate 1.2mL / min), an injection port temperature of 250℃, a detector temperature of 280℃, and a programmed temperature ramp mode—an initial temperature of 80℃ held for 3 min, then increased to 180℃ at a rate of 10℃ / min and held for 5 min. The injection volume was 1.0μL, and the split ratio was 20:1. Regarding key parameters, the test conditions were ambient temperature and pressure, and the sample needed to be thoroughly mixed and measured in triplicate. Data processing employed the area normalization method to calculate the mass percentage of each component, and the average of three measurements was taken as the final result.
[0225] Experiment 2: Determination of Adsorption Selectivity Coefficient
[0226] This experiment used the modified 13X molecular sieve adsorbent and raw material mixture prepared in this invention as the test object to evaluate the selective adsorption capacity of the adsorbent for 1,3-dichlorobenzene relative to 1,2-dichlorobenzene and 1,4-dichlorobenzene. The equilibrium adsorption capacity of the adsorbent for different isomers was determined by static adsorption equilibrium method, and the selectivity coefficient was calculated. The specific experimental method was as follows: 1.0 g of pretreated adsorbent was weighed and placed in a sealed container, and 20 mL of a known dichlorobenzene isomer mixture (1,3-dichlorobenzene mass fraction 50 wt%) was added. The mixture was kept at 120℃±2℃ and shaken for 8 h until adsorption equilibrium was reached. After separating the liquid phase, the concentration of each isomer in the liquid phase was determined by gas chromatography, and the solid phase adsorption capacity was calculated based on mass conservation. The key parameters were: shaking speed 150 rpm, and the test was repeated 3 times. In data processing, the selectivity coefficient α is defined as (q1 / C1) / (q2 / C2), where q is the amount of solid-phase adsorption, C is the liquid-phase equilibrium concentration, subscript 1 represents 1,3-dichlorobenzene, and subscript 2 represents other isomers. The mean ± standard deviation is taken as the final result.
[0227] Experiment 3: Adsorbent Cyclic Stability Test
[0228] This experiment used the modified 13X molecular sieve adsorbent prepared according to this invention as the test object, aiming to investigate the performance retention rate of the adsorbent after multiple adsorption-desorption-regeneration cycles and verify its long-term stability. The experiment was conducted under actual process conditions, with multiple cycles, each cycle including adsorption, desorption, and regeneration steps, and the changes in selectivity and adsorption capacity were monitored. The specific experimental method was as follows: 5g of adsorbent was loaded into a small fixed-bed device, and adsorption (120℃, 1.10MPa) and desorption (ethylbenzene, 130℃) were performed according to the conditions described in this experiment. Regeneration involved rinsing with desorbent (130℃) and drying (105℃, 7h), and this process was repeated 50 times. Samples were taken every 10 cycles to determine the selectivity and adsorption capacity. The key parameter was approximately 12h per cycle, with a test period of 25 days. Data processing included calculating the performance retention rate (%) of the 50th cycle relative to the 1st cycle and plotting the performance change curve with the number of cycles to visually demonstrate the stability trend.
[0229] Experiment 4: Adsorbent Particle Compressive Strength Test
[0230] This experiment used the modified 13X molecular sieve adsorbent particles prepared according to this invention as the test object to evaluate the mechanical strength of the adsorbent particles and ensure that they are not easily broken during simulated moving bed loading and operation. The experiment involved applying pressure to individual particles until they broke, recording the breakage load, and calculating the compressive strength. The specific experimental method was as follows: using an intelligent particle strength tester, 30 adsorbent particles with the same sieve size (±0.05 mm) were randomly selected. The particles were placed between two parallel pressure plates, and pressure was applied at a constant rate (2 mm / min) until the particles broke. The maximum load at breakage was recorded. Key parameters included an ambient temperature of 25±2℃, a relative humidity of 50±10%RH, and samples equilibrated at room temperature for 24 hours before testing. In data processing, the compressive strength (N / particle) was equal to the average breakage load. After removing the maximum and minimum values, the average value ± standard deviation was calculated. Simultaneously, the breakage rate, i.e., the proportion of particles with breakage loads below a set threshold, was also calculated.
[0231] Experiment 5: Characterization of mesoporous structures (BJH method)
[0232] This experiment used the modified 13X molecular sieve adsorbent prepared according to this invention as the test object, aiming to quantitatively determine the mesopore volume and pore size distribution of the adsorbent and verify the mesoporization effect of alkali treatment. The experiment was based on the adsorption-desorption isotherm of nitrogen at 77 K, and the BJH model was applied to calculate the mesopore size distribution and pore volume from the desorption branch. The specific experimental method was as follows: using a fully automated specific surface area and pore size analyzer, the sample was pretreated by vacuum degassing at 300℃ for 6 h to remove adsorbed water and impurities. Approximately 0.2 g of sample was weighed, and the nitrogen adsorption-desorption isotherm was measured at liquid nitrogen temperature (77 K) with a relative pressure P / P0 range of 0.05 to 0.99. The cumulative pore volume in the range of 2 to 50 nm was calculated based on the desorption branch using the BJH method. The key parameters were degassing temperature 300℃, degassing time 6 h, and test temperature 77 K. Data processing automatically calculates mesoporous pore volume (cm³ / g), average pore size (nm), and pore size distribution curves, comprehensively characterizing the mesoporous structure.
[0233] Experiment 6: Determination of poly(4-vinylpyridine) grafting amount (thermogravimetric analysis)
[0234] This experiment used the modified 13X molecular sieve adsorbent prepared in this invention and the epoxy silanization intermediate before grafting as test objects, aiming to quantitatively determine the actual grafting amount of poly(4-vinylpyridine) in the adsorbent through thermogravimetric analysis (TGA). The experiment utilized the principle that poly(4-vinylpyridine) undergoes thermal decomposition at high temperatures, leading to mass loss, and calculated the grafting amount by comparing the difference in thermogravimetric analysis before and after grafting. The specific experimental method was as follows: using a thermogravimetric analyzer, 10 mg of sample was weighed and heated from room temperature to 800℃ at a rate of 10℃ / min under a nitrogen atmosphere (flow rate 50 mL / min, purity 99.99%), and the sample mass change curve with temperature was recorded. Key parameters included a nitrogen flow rate of 50 mL / min, a heating rate of 10℃ / min, and a temperature range of 25℃ to 800℃. In data processing, the polymer grafting amount (wt%) is equal to the percentage of mass loss of the sample after grafting in the 300℃ to 650℃ range minus the percentage of mass loss of the intermediate before grafting in the same temperature range. This difference is the actual content of the grafted polymer.
[0235] Figure 1 The XRD patterns are obtained by powder X-ray diffraction of 13X molecular sieve samples from Examples 1, Comparative Examples 1 and 2, showing the intensity as a function of 2θ. The basic parameters are: radiation source Cu Kα, scanning range covering the main characteristic peak range, step scanning, and intensity normalization. The variable parameters are the differences in lattice constant and peak shape caused by the different sodium-potassium ratios in the samples. The results show that the characteristic peak positions and shapes of Example 1 are more concentrated, the half-peak width is smaller, and the crystallinity is better maintained. In contrast, Comparative Examples 1 and 2 show more obvious peak position shifts and peak shape broadening, proving that sodium-potassium synergistic regulation can optimize the microporous environment while maintaining lattice order, thereby improving structural stability and the basis for subsequent shape selection.
[0236] Figure 2 This is a high-resolution XPS scan of sodium (Na) in Example 1, Comparative Example 1, and Comparative Example 2. XPS was used to perform high-resolution scanning of the Na-related energy level range to obtain the surface Na signal. The basic parameters were a monochromatic Al Kα excitation source, consistent energy calibration, and the use of the same background subtraction and peak fitting integration method. The variable parameters were the differences in Na peak area, intensity, and shape caused by different ion exchange conditions. The results show that the Na signal intensity and area changes in Example 1 better conform to the target control trend, while the Na signal in the comparative sample deviates from this trend. This demonstrates that ion exchange can effectively regulate the surface Na content, providing a basis for optimizing the microporous electrostatic environment.
[0237] Figure 3The image shows a high-resolution XPS scan of potassium (K) in Example 1, Comparative Example 1, and Comparative Example 2. XPS was used to perform high-resolution scanning of the K-related energy level range to obtain surface K signals. The basic parameters were a monochromatic Al Kα excitation source, consistent energy calibration, and the use of the same background subtraction and peak fitting integration method. The variable parameters were the differences in K peak area, intensity, and shape caused by different ion exchange conditions. The results show that the synergistic relationship between the K and Na signals in Example 1 is more stable, while the K signal intensity or area ratio in the comparative sample deviates. This demonstrates that mixed ion exchange can achieve controllable adjustment of the surface K content, thus supporting the synergistic optimization and rationality of the cation composition on the material surface.
[0238] Figure 4 The BJH method plots of nitrogen adsorption-desorption isotherms are shown. Examples 1, 3, and 4 were obtained by nitrogen adsorption-desorption tests at 77 K, showing the adsorption capacity as a function of relative pressure P / P0. The basic parameters were consistent pre-degassing conditions for the samples, test relative pressure covering the low-pressure to high-pressure range, and recording of adsorption and desorption branches. The variable parameter was the difference in mesoporous degree caused by different alkali treatment intensities. The results showed that Example 1 had clear mesoporous hysteresis characteristics and the overall adsorption behavior took into account both low-pressure microporous adsorption and medium-high pressure mesoporous contributions. Comparative Example 3 showed insufficient hysteresis and mesoporous contribution, while Comparative Example 4 showed significantly enhanced adsorption in the medium-high pressure region with signs of structural damage. This demonstrates that moderate mesoporousization can form effective mass transfer channels while maintaining microporous characteristics, which is beneficial for achieving a synergy between mass transfer rate and shape selection selectivity.
[0239] Figure 5 The BJH pore size distribution curves of the nitrogen adsorption-desorption isotherm are shown. Based on the nitrogen desorption branches of Example 1, Comparative Example 3, and Comparative Example 4, the differential pore size distribution curves in the 2–50 nm mesopore range were calculated using the BJH method. The basic parameters were the same BJH calculation model and the same pore size range, consistent data smoothing and baseline processing, and output with continuous pore size coordinates. The variable parameters were the pore size distribution peak position, peak intensity, peak width, and the change of the dominant mesopore size. The results show that Example 1 exhibits a more concentrated and clearly defined peak distribution in the mesopore range, Comparative Example 3 has a weaker distribution contribution, while Comparative Example 4 has a wider distribution and indicates excessive dissolution of the indicator structure. This proves that the mesopore size of Example 1 is more controllable, which is beneficial for balancing the construction of mass transfer channels and the maintenance of framework integrity.
[0240] Figure 6The BJH cumulative pore volume distribution curve of the nitrogen adsorption-desorption isotherm is shown. Based on the nitrogen desorption branches of Example 1, Comparative Example 3, and Comparative Example 4, the cumulative pore volume as a function of pore size was obtained by integrating the 2–50 nm mesoporous range using the BJH method. The basic parameters were the same integration interval and the same pore volume calculation rule, and the pretreatment and testing conditions of each sample were kept consistent. The variable parameters were the growth rate of the cumulative pore volume and the mesoporous pore volume level reflected by the final cumulative pore volume size. The results show that the cumulative pore volume growth of Example 1 was moderate and the change was smooth, the cumulative pore volume of Comparative Example 3 was low, and the cumulative pore volume of Comparative Example 4 grew too fast, indicating excessive mesoporous formation. This proves that Example 1 achieved a reasonable mesoporous pore volume configuration, which can improve diffusion and accessibility while avoiding significant damage to the microporous framework.
[0241] Figure 7 This is a comparison chart of the grafting amount of poly(4-vinylpyridine) measured. The actual grafting amount of poly(4-vinylpyridine) in Example 1 and Comparative Examples 5, 6, and 7 was calculated by thermogravimetric analysis of the organic weight loss difference in the range of 300–650℃, and expressed as mean and standard deviation. The basic parameters were the same heating program and atmosphere conditions, and the same interval integration rule was used. The variable parameters were the different final organic loads caused by the grafting material and reaction conditions. The results show that the grafting amount in Example 1 is at a moderate level and corresponds to better overall performance. The insufficient grafting in Comparative Example 5 leads to insufficient modification effect. The excessive grafting in Comparative Example 6 may cause pore burden and regeneration difficulties. Comparative Example 7 lacks a grafted layer and is difficult to obtain enhanced recognition effect. This proves that the grafting amount is controllable and there is a reasonable optimization range, supporting the necessity and effectiveness of surface chemical regulation strategy.
[0242] Figure 8 This is a macroscopic optical photograph of the adsorbent in Example 1. The basic parameters are: the sample was subjected to sodium-potassium mixed ion exchange and alkali treatment to create mesoporous particles, followed by epoxy silane grafting and polyvinylpyridine covalent grafting, then dried at 105°C and sieved into adsorbent particles; the light source and background are consistent. The variable parameters are the combined effects of polyvinylpyridine mass fraction (4.5 wt%), Na:K mass ratio (1.2:1), and mesopore volume (0.18 cm³ / g) on appearance brightness and uniformity. The conclusion is that the sample is a grayish-white to off-white matte particle with uniform color and shape, and no obvious macroscopic cracking or powdering agglomeration. This indicates that the wet exchange and grafting process can maintain the integrity of the particle shape and batch consistency at the particle scale, providing a reasonable appearance and morphology basis for subsequent simulated stable filling and recycling of moving beds.
[0243] Figure 9The image shown is a scanning electron microscope (SEM) image of the adsorbent in Example 1. The basic parameters were SEM observations of the adsorbent particles from low to high magnification, including surface and, if necessary, cross-sectional observations, and recording of crystal units and pore structures. The variable parameters were the alkaline treatment conditions for mesoporization (sodium hydroxide concentration 0.12 mol / L, temperature 60°C, time 1.2 h) and the effects of subsequent hydrochloric acid neutralization, epoxy silane grafting, and polyvinylpyridine covalent grafting on crystal shape retention and surface roughness. The conclusion is that at low magnification, the particle surface is covered with a continuous network of through-cracks. At medium and high magnification, micron-sized molecular sieve crystals or aggregates are visible, accompanied by nanoscale pits and pore features, and the crystal edges are still discernible. No obvious sintering neck growth is observed. This indicates that mesoporization introduces mass transfer channels that can reach the mesopore scale while maintaining the granular structure of the molecular sieve framework. The grafted layer does not cause serious pore obstruction. Structurally, it supports both mass transfer efficiency and bed mechanical stability under liquid-phase adsorption at 120°C and desorption at 130°C.
[0244] Figure 10 The images shown are transmission electron microscopy (TEM) images of the adsorbent in Example 1. The basic parameters are bright-field morphology observation of molecular sieve crystals or thin regions using TEM and high-resolution imaging of local areas, combined with selected area electron diffraction (SEED) to determine crystallinity. The variable parameters are the degree of pore evolution inside the crystal caused by alkali treatment and the influence of the distribution of organic phases formed by epoxy silane grafting and poly(4-vinylpyridine) covalent grafting on the outer surface and mesopore entrance on the interface clarity and lattice visibility. The conclusion is that the bright-field image shows the existence of interconnected nanopores inside the crystal with continuous pore walls. The high-resolution image shows clear lattice fringes that are consistent with the characteristic interplanar spacing of FAU-type molecular sieves, and the diffraction characteristics show that the crystalline state is dominant. This indicates that alkali treatment mainly introduces hierarchical pores without causing overall amorphization of the framework. The grafting process is mainly surface functionalization while the framework crystallinity is well maintained. From the microstructure level, this supports the rationality of the design of the adsorbent, which has both selective sites and fast diffusion channels.
[0245] Table 1. Performance comparison data between the examples and comparative examples.
[0246] Example 1 99.50±0.08 3.85±0.15 4.20±0.18 94.5±1.2 28.5±2.1 0.18±0.01 4.5±0.2 Example 2 99.30±0.10 3.52±0.18 3.85±0.20 92.8±1.5 25.2±2.5 0.12±0.01 2.5±0.2 Example 3 99.75±0.06 4.10±0.12 4.52±0.15 95.8±0.9 30.8±1.8 0.24±0.01 6.5±0.3 Example 4 99.60±0.07 3.98±0.14 4.35±0.16 96.2±1.0 32.5±1.6 0.20±0.01 7.5±0.3 Comparative Example 1 98.65±0.15 2.95±0.22 3.20±0.25 88.5±2.0 26.8±2.8 0.18±0.01 4.5±0.2 Comparative Example 2 98.80±0.14 3.15±0.20 3.45±0.22 89.2±1.8 27.2±2.6 0.18±0.01 4.5±0.2 Comparative Example 3 98.20±0.18 3.50±0.19 3.82±0.21 85.5±2.5 32.0±1.5 0.03±0.00 4.5±0.2 Comparative Example 4 98.55±0.16 3.20±0.21 3.50±0.23 82.0±2.8 21.5±3.2 0.35±0.02 4.5±0.2 Comparative Example 5 98.90±0.12 3.45±0.17 3.75±0.19 90.0±1.6 27.8±2.3 0.18±0.01 0.2±0.1 Comparative Example 6 98.70±0.14 3.60±0.18 3.92±0.20 78.5±3.2 26.0±2.9 0.18±0.01 9.0±0.4 Comparative Example 7 98.45±0.17 3.28±0.20 3.58±0.22 91.5±1.5 28.0±2.2 0.18±0.01 0.0±0.0 Comparative Example 8 97.80±0.20 2.80±0.25 3.05±0.28 93.0±1.4 28.2±2.2 0.18±0.01 4.5±0.2
[0247] As can be seen from the performance of the examples and comparative examples in Table 1, this invention achieves an excellent balance between 1,3-dichlorobenzene separation purity, adsorption selectivity, cycling stability, and particle mechanical strength through a four-step synergistic modification strategy: sodium-potassium mixed ion exchange to regulate the microporous cation environment, alkali treatment to form an appropriate amount of mesopores to improve the mass transfer rate, epoxy silane grafting to construct covalent anchoring sites, and poly(4-vinylpyridine) grafting to enhance surface polarity recognition ability. The product purity of all four examples reached over 99.30 wt%, and the selectivity coefficient α... 13 / 12Between 3.52 and 4.10, the performance retention rate after 50 cycles was above 92.8%, and the particle compressive strength was between 25.2 and 32.5 N / particle, significantly better than the comparative examples. Comparative examples 1 and 2 suffered from decreased micropore selectivity due to the Na:K ratio deviating from the optimized range; comparative example 3 suffered from impaired mass transfer due to insufficient mesopores; comparative example 4 suffered from micropore structure damage due to excessive mesoporization; comparative example 5 suffered from poor surface modification effect due to insufficient polymer grafting; comparative example 6 suffered from pore blockage and regeneration difficulties due to excessive grafting; comparative example 7 could not achieve surface polarity control due to the lack of a polymer graft layer; and comparative example 8 suffered from insufficient kinetic mass transfer rate due to excessively low adsorption temperature. The performance degradation of these technical solutions fully demonstrates the synergistic necessity and irreplaceability of the parameter ranges and modification steps in the technical solution of this invention.
[0248] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for adsorption-desorption separation, purification, and refining of m-dichlorobenzene, characterized in that, Includes the following steps: S1. Providing a raw material mixture comprising 1,3-dichlorobenzene and at least one dichlorobenzene isomer selected from 1,2-dichlorobenzene and 1,4-dichlorobenzene; S2. Under adsorption conditions of 60 to 180°C and absolute pressure of 0.20 to 2.00 MPa, the raw material mixture is contacted with an adsorbent to obtain a non-adsorbed phase and an adsorbed phase. The adsorbent comprises a modified 13X molecular sieve material. The modification includes: subjecting the 13X molecular sieve to sodium and potassium ion mixed exchange so that the mass ratio of elemental sodium to elemental potassium in the adsorbent is 0.65:1 to 2:1; subjecting it to alkali treatment to form mesopores so that the mesopore volume of the adsorbent is 0.05 to 0.30 cm³ / g; introducing an epoxy-containing organosilane graft layer on the surface of the molecular sieve; and causing poly(4-vinylpyridine) to undergo a ring-opening reaction with the epoxy groups to form covalent bonds with the surface of the molecular sieve. The epoxy-containing organosilane is 3-glycidyl etheroxypropyltrimethoxysilane, and the mass fraction of poly(4-vinylpyridine) in the adsorbent is 0.5 wt% to 8.0 wt%. S3. Desorb the adsorbed phase using a desorbent to obtain a 1,3-dichlorobenzene enriched stream, wherein the desorbent is selected from one or both of ethylbenzene and n-propylbenzene; S4. The 1,3-dichlorobenzene enriched stream is subjected to desorbent separation and recovery to obtain the 1,3-dichlorobenzene product and the desorbent is recovered for recycling.
2. The method according to claim 1, characterized in that, Steps S2 and S3 are performed in a simulated moving bed system.
3. The method according to claim 1, characterized in that, The desorption temperature in step S3 is 60 to 200°C, the mass fraction of 1,3-dichlorobenzene in the raw material mixture is 30 wt% to 80 wt%, and the mass ratio of the desorbent to the raw material mixture is 0.5:1 to 5.0:
1.
4. The method according to claim 1, characterized in that, The desorbent separation and recovery in step S4 is carried out by distillation separation. The adsorbent is regenerated periodically during continuous operation. The regeneration includes rinsing the adsorbent with the desorbent at a temperature of 60 to 200°C and then drying it. The mass fraction of the 1,3-dichlorobenzene product is 99.0 wt% to 99.95 wt%.
5. The method according to claim 1, characterized in that, The adsorbent is prepared by the following steps: a) The 13X molecular sieve is subjected to sodium and potassium ion mixed exchange, such that the mass ratio of elemental sodium to elemental potassium in the adsorbent is 0.65:1 to 2:
1. b) subject the molecular sieve treated in step a) to alkali treatment to form mesopores, such that the mesopore volume of the adsorbent is 0.05 to 0.30 cm³ / g; c) Introduce an epoxy-containing organosilane graft layer on the surface of the molecular sieve, wherein the epoxy-containing organosilane is 3-glycidyl etheroxypropyltrimethoxysilane. d) The poly(4-vinylpyridine) undergoes a ring-opening reaction with the epoxy group to form a covalent bond with the surface of the molecular sieve.
6. The method according to claim 5, characterized in that, The 13X molecular sieve intermediates described in steps a) and b) after mixing, exchange, and mesoporization were prepared by the following steps: A1. Raw material preparation: 13X molecular sieve is used as a solid raw material; sodium chloride and potassium chloride are dissolved in water to obtain an ion exchange solution, wherein the concentration of sodium chloride is 0.10 to 2.00 mol / L and the concentration of potassium chloride is 0.05 to 1.50 mol / L; A2. Mixed ion exchange: The 13X molecular sieve is contacted with the ion exchange solution and kept at a temperature of 60 to 95°C for 1.0 to 3.0 h, and repeated 1 to 3 times; A3. Washing and drying: The solid is washed with the water and dried to obtain a molecular sieve after mixed ion exchange; A4. Alkali treatment for mesoporization: The solid obtained in step A3 is contacted with an aqueous solution of sodium hydroxide, wherein the concentration of sodium hydroxide is 0.05 to 0.20 mol / L, and the contact is maintained at a temperature of 50 to 70°C for 0.5 to 2.0 h. A5. Neutralization and post-treatment: The solid-liquid system was neutralized with an aqueous solution of hydrochloric acid to a pH of 6.0 to 8.0, followed by washing and drying to obtain the intermediate; The intermediate satisfies the following conditions: the mass ratio of sodium to potassium in the obtained solid is 0.65:1 to 2:1 and the mesopore volume is 0.05 to 0.30 cm³ / g.
7. The method according to claim 6, characterized in that, The epoxy-containing organosilane graft layer in step c) is prepared by the following steps: B1. Raw material preparation: The intermediate described in claim 6 is dispersed in a solvent system, wherein the solvent system comprises ethanol and water, the volume ratio of ethanol to water is 70:30 to 95:5, and the solid-liquid ratio of the intermediate to the solvent system is 1g solid to 5 to 30mL solvent; B2. pH adjustment: The apparent pH of the solvent system was adjusted to 4.0 to 6.0 using acetic acid; B3. Silanization reaction: 3-glycidyl etheroxypropyltrimethoxysilane is added to the solvent system in an amount of 0.5 wt% to 5.0 wt% relative to the dry basis mass of the intermediate, and the reaction is carried out at a temperature of 30 to 60 °C for 1 to 6 h. B4. Post-processing: Wash and dry to obtain epoxy silanized intermediate; The mass increment of the epoxy silanization intermediate relative to the intermediate used in step B1 is 0.1 wt% to 2.0 wt%.
8. The method according to claim 7, characterized in that, The poly(4-vinylpyridine) covalent graft described in step d) is prepared by the following steps: C1. Raw material preparation: The epoxy silanization intermediate is dispersed in a mixed solvent, wherein the mixed solvent contains ethanol and acetic acid, and the volume ratio of ethanol to acetic acid is 95:5 to 80:20, and the solid-liquid ratio of the epoxy silanization intermediate to the mixed solvent is 1g solid to 5 to 30mL solvent. C2. Grafting reaction: Poly(4-vinylpyridine) is added to the mixed solvent in an amount of 0.5 wt% to 8.7 wt% relative to the dry basis mass of the epoxy silanization intermediate, and the reaction is carried out at a temperature of 40 to 90 °C for 2 to 12 h. C3. Washing and drying: Washing to remove unbound poly(4-vinylpyridine) and drying at a temperature of 60 to 120°C to obtain the adsorbent.
9. The method according to claim 5, characterized in that, The adsorbent is pretreated before being used for adsorption-desorption separation, the pretreatment including drying at a temperature of 60 to 150°C for 2 to 12 hours.
10. The method according to claim 5, characterized in that, The adsorbent has a sieve particle size of 0.30 to 1.60 mm.
Citation Information
Patent Citations
Hydrophobic silicalite method for liquid-phase selective adsorption, separation and mixing of dichlorobenzene
CN1315217A